Effect of Neuromuscular Electrical Stimulation Training on the Finger Extensor Muscles for the Contralateral Corticospinal Tract in Normal Subjects: A Diffusion Tensor Tractography Study - Jang, Sung Ho; Seo, You Sung (Frontiers in Human Neuroscience, 2018)
Objectives: Neuromuscular electrical stimulation (NMES) is a popular rehabilitative modality to improve motor function of the extremities and trunk. In this study, we investigated changes of hand function and the contralateral corticospinal tract (CST) with treatment by NMES on the finger extensor muscles for two weeks, using serial diffusion tensor tractography (DTTs). Methods: Thirteen right handed normal subjects were recruited. Treatment was applied to the left hand (the NMES side), and the right hand was the control side. NMES was applied for 30min/day, seven days per week, for two weeks. Hand motor function was evaluated twice at pre-NMES and post-NMES training using grip strength (GS), Purdue pegboard test (PPT), and tip pinch. The fractional anisotropy (FA) and tract volume (TV) of the CST in both hemispheres were measured using DTT. Results: On the control side, the clinical scores did not differ significantly between pre- and post-NMES training (p>0.05). However, on the NMES side, PPT and tip pinch improved significantly (p<0.05), although GS did not. TV of the right CST increased significantly at post-NMES training (p<0.05) whereas FA did not differ significantly (p>0.05). By contrast, FA and TV on the left CST did not change significantly (p>0.05). Conclusion: We demonstrated facilitation of the contralateral CST with improvement of fine motor activity by two weeks of NMES training of peripheral muscles in normal subjects. We think our results can be applied to the normal subjects and patients with brain injury to improve the fine motor function of the hand and facilitate the normal CST or healing of the injured CST.